Biology and systematics of Trogoderma species with special reference to morphological and molecular diagnostic techniques for identification of Trogoderma pest species - Castalanelli, Mark A. (Curtin University, 2011)
The genus Trogoderma contains some of the world’s most serious invasive pests of wheat and other stored grain products. Even with the application of strict quarantine measures, these grain beetles still find their way into new countries and cause imposition of onerous restrictions on exports. Two of the most serious Trogoderma pest species are Trogoderma granarium Everts and Trogoderma variable Ballion. At present both species can only be reliably identified by a limited number of highly skilled diagnosticians trained in traditional morphological based keys. To differentiate between these two species, delicate dissections of the genitalia and mouthparts are required. These dissections can take over an hour, even for skilled diagnosticians. However, accurate identification of larvae or a damaged specimen is difficult. To overcome these identification problems, the use of molecular markers in differentiating Trogoderma species was investigated.In Australia, T. variabile is regarded as a minor yet persistent pest, but is considered a concern as it could mask the presence of T. granarium. To track the distribution of T. variabile the Commonwealth Scientific and Industrial Research Organisation (CSRIO) conducted a national trapping program from 2001 to 2003. Using partial sequences of two mitochondrial genes (Cytochrome Oxidase I and Cytochrome b) and the nuclear gene (18S), these samples were used in a phylogenetic study to examine the distribution, dispersal pathways, and species boundaries of T. variabile. Based on the molecular results, only 47% of the samples analysed were T. variabile, and the remaining were a mixture of six putative species. Unfortunately, all specimens were macerated to extract the DNA and so it was not possible to reexamine the specimens morphologically to confirm their identity.A non-destructive DNA extraction method is an important step in ensuring samples can be re-examined when molecular and morphological results are incongruent. Using EDNA HiSpEx, a rapid and non-destructive DNA extraction technique for arthropod specimens was developed. This technique was tested on four arthropod orders, using specimens that were fresh, preserved by air drying, stored in ethanol, or collected with sticky or propylene glycol traps. The extraction could be completed in 20 minutes for Coleoptera, Diptera and Hemiptera, and two minutes for the subclass Acarina, without significant distortion, discolouration, or other damage to the specimens. All samples analysed hereafter had their DNA extracted using this method.Using partial sequences of two mitochondrial genes, Cytochrome Oxidase I and Cytochrome b, and the nuclear gene, 18S, a phylogenetic study was conducted to differentiate T. granarium from T. variabile and other closely related species that were collected from across Australia. The aim of this study was to generate a reference database that could serve as a frame of reference for the identification of quarantine intercepts, rediscover the putative species reveal in the CSIRO trapping program, and evaluate the existing morphologically-based polyphyletic positioning of Trogoderma. Molecular phylogenetic reconstruction revealed that the Trogoderma genus was paraphyletic. However, this finding was only supported by Bayesian analysis because Parsimony analysis exhibited polytomy and the putative species identified in the CSIRO trapping program were not rediscovered in this study. The sequence data was also used to estimate time to most recent common ancestor for Trogoderma and four closely related genera from the Megatomini and Attagenini tribes. Estimation of Dermestidae origins exceeded 175 million years, placing the origins of this family in Pangaea.Without an extensive sampled database that has both phylogenetic and morphological support, using a DNA barcoding approach could lead to inaccurate identification of intercepted material. Furthermore, DNA barcoding is time consuming when DNA sequences need to be processed offsite, with results within days rather than hours. The aim was to develop a PCR test that had high sensitivity and specificity. A quantitative PCR test was developed by multiplexing hydrolysis probes, amplification controls, and including a melt curve analysis step. As well as accurate identification of T. variabile and T. granarium, this multiplex test provided an internal checking system thereby reducing the incidence of false positives and false negatives.This study highlights the importance of combining both molecular methods and morphological characteristics. With out morphological data, it is difficult to ascertain when molecular results are incongruent because there is no standard genetic measure that can be used to separate a species. Likewise, morphological taxonomy needs to be checked by molecular markers as to ensure important morphological characters are not overlooked and that morphologically similar species are not grouped together. Only once both methods are combined can a pest species be accurately diagnosed.